2006
DOI: 10.1038/sj.mp.4001867
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and genetic evidence supports a role for the kainate-type glutamate receptor gene, GRIK4, in schizophrenia and bipolar disorder

Abstract: In the search for the biological causes of schizophrenia and bipolar disorder, glutamate neurotransmission has emerged as one of a number of candidate processes and pathways where underlying gene deficits may be present. The analysis of chromosomal rearrangements in individuals diagnosed with neuropsychiatric disorders is an established route to candidate gene identification in both Mendelian and complex disorders. Here we describe a set of genes disrupted by, or proximal to, chromosomal breakpoints (2p12, 2q3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 67 publications
4
78
0
1
Order By: Relevance
“…Furthermore, duplication of the GluK4 gene has been associated with autism [138] and, consistent with this, overexpression of GluK4 in the forebrain of mice causes severe anxiety and ASD-like behaviours [139]. Additionally, GluK4 has been linked with treatment-resistant depression [140], and disruption of the gene encoding GluK4 has been observed in a patient with schizophrenia and mental retardation [141].…”
Section: Kars and Other Neurological Disordersmentioning
confidence: 85%
“…Furthermore, duplication of the GluK4 gene has been associated with autism [138] and, consistent with this, overexpression of GluK4 in the forebrain of mice causes severe anxiety and ASD-like behaviours [139]. Additionally, GluK4 has been linked with treatment-resistant depression [140], and disruption of the gene encoding GluK4 has been observed in a patient with schizophrenia and mental retardation [141].…”
Section: Kars and Other Neurological Disordersmentioning
confidence: 85%
“…[23][24][25][26] Overall, the quality and reproducibility of this genotyping was extremely high-the proprietary quality assessment score ('GenCall') was high for every analysed NPAS3 SNP marker. Moderate deviation from the Hardy-Weinberg equilibrium was observed for four markers in the control group, but in no instance did these correspond to significant P-values in the case-control analysis (Table 1).…”
Section: Association Studymentioning
confidence: 99%
“…The provenance of the DNA samples has been described elsewhere, [23][24][25][26] but, in brief, it comprises patients of hospitals in southeast and south central Scotland and controls of matching geographical distribution obtained primarily from the Scottish National Blood Transfusion Service. Case diagnoses were made according to the DSM-IV criteria, based on case note review and interview using The Schedule for Affective Disorders and Schizophrenia-lifetime version (SADS-L).…”
Section: Association Studymentioning
confidence: 99%
“…Of those genes which have been reasonably well- Recent evidence has suggested a protective effect of variation in the kainate class ionotropic glutamate receptor gene GRIK4 (Pickard et al, 2006, Pickard et al, 2008b. After detecting a complex chromosomal translocation in a patient with schizophrenia and learning disability, Pickard and colleagues (Pickard et al, 2006) noted that one of the genes disrupted by the translocation was GRIK4 on chromosome 11. They subsequently showed that a 14 base-pair insertion/deletion polymorphism in the 3′ UTR of the gene was strongly associated with a reduced risk of BPD (p = 1.9 × 10 −7) ) in a case-control study and found supportive evidence in a second case-control sample (p = .011) (Pickard et al, 2008b).…”
mentioning
confidence: 99%
“…Subsequent association studies have implicated a variety of markers on the DISC1 gene with schizophrenia and BPD (Hodgkinson et al, 2004, Palo et al, 2007, Hennah et al, 2008. Other translocations segregating with bipolar or psychotic illness have implicated additional genes including GRIK4 and NPAS3 (Pickard et al, 2006, Pickard et al, 2008a.Deletions or duplications of a small part of a chromosome (in the range of 1 kb to several megabases (Mb)), may also play an important role in the aetiology of psychiatric disorder. These copy number variants (CNVs) include the well-known 1.5-3 Mb deletion on 22q11 that produces velo-cardio-facial syndrome (VCFS), one expression of which is a 25-30-fold increased risk for psychotic disorders (Murphy, 2002).…”
mentioning
confidence: 99%